EFEKTIVITAS METODE STORYTELLING BERBANTUAN TUTOR SEBAYA UNTUK MENINGKATKAN KETERAMPILAN BERBICARA ANAK DENGAN HAMBATAN EMOSI DAN PERILAKU - Radiah, Radiah; Marlina, Marlina; Rahmahtrisilvia, Rahmahtrisilvia; Mahdi, Arisul (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Children with emotional and behavioral disabilities generally experience challenges such as a tendency to be tense, withdrawn, lacking self-confidence, quiet, easily bored, and having difficulty expressing their opinions and feelings. Based on the results of an assessment conducted at an inclusive school, one student demonstrated a lack of speaking skills. The results of the identification and assessment conducted by the researcher were based on the special needs children identification instrument and speaking skills assessment. The purpose of this study was to test the effectiveness of the peer tutor-assisted storytelling method in improving the speaking skills of children with emotional and behavioral disabilities. The selection of research subjects used the special needs children identification instrument and speaking skills assessment. This study used a single subject research form with a multiple baseline cross-variable design. The research subject was one person with four aspects: pronunciation, vocabulary, structure, and self-confidence. Data were collected through oral tests and the tools used were speaking skills instruments and data processing used were percentages. Data analysis was made in the form of visual graphic analysis consisting of analysis within conditions and analysis between conditions. The results showed an increase in speaking skills in children after being given the peer tutor-assisted storytelling method.